Novel bismuth oxy hydride chromate (HBi3(CrO4)O3) nano-sheets/rods synthesized by one step one pot wet chemical method. (2nd June 2021) - Manjunatha, Channegowda
Abstract: A novel inorganic hydride material, hydrogen bismuth chromium oxide (HBi3 (CrO4 )O3 ), with 2D nano sheets and 1D nanorods were prepared for the first time using a simple, green, hazard free hydrothermal method. The X-ray diffraction (XRD) results confirms that the as-formed sample (HBi3 (CrO4 )O3 ) has monoclinic crystal system with a space group of P21/a. The field emission scanning electron microscope (FESEM) analysis clearly reveal that the new material contains large quantity of 2D nanosheets of thickness <10 nm and spread over >1000 nm and with small amounts of micro-rods of width in the range of 1 to 5 μ m and lengths in the range of 40 to 100 μ m. The EDS analysis confirms the presence of 'Bi', 'Cr', and 'O' and it further evidences the purity of the sample. The fourier transform infra-red (FT-IR) spectra evidences that the sample has Bi-H, Bi-O and Cr-O bonds as expected for HBi3 (CrO4 )O3 . This material has a potential to find its place in hydrogen storage material, photo/electro catalysis, fuel cells, optoelectronics and rechargeable batteries, therefore it needs materials researcher attention immediately.